IMPORTANCE OF THE TRICHOSCOPY IN SCALP DYSESTHESIA - Maria Bibiana Leroux (Our Dermatology Online, 2013)
The trichoscopy has been incorporated as a first hand method in patients consulting for scalp problems. Magnifying glass or digital microscope that permit the direct visualization of the hair shaft and the perifolicullar skin are utilized to diagnose cicatricial and non-cicatricial alopecia. A female patient with an alopecia plaque associated with a scalp dysesthesia in which trichoscopy was very useful in its diagnosis is presented.